PENGARUH PEMBELAJARAN PROBLEM BASED LERANING (PROBLEM BASED LEARNING DAN PROJECT BASED LEARNING SERTA MOTIVASI BELAJAR TERHADAP PERKEMBANGAN KOGNITIF ANAK - Fitriyani, Heni; Sabariah; Zaman, Akhmad Qomaru (Universitas Negeri Medan, 2025)
Abstract: Basic learning becomes effective through play, exploration, and differentiation, using the PBL and PjBL approaches along with high motivation to enhance children's cognition, creativity, and engagement. The purpose of this study is to measure the effectiveness of two learning models and learning motivation on the cognitive improvement of children who are beginning to develop abstract thinking and problem-solving skills. The research method uses a quantitative approach with a pretest-posttest control group experimental design, random sampling, the use of questionnaires, observations, cognitive tests, normality tests, homogeneity tests, Two-Way ANOVA analysis, Tukey post-hoc test, and multiple linear regression analysis. The results show a significant influence of learning methods and learning motivation on children’s cognitive scores. The combination of both factors and their interaction statistically strongly affect cognitive development with a predictive power of 88.1%. These findings confirm that the effectiveness of learning methods depends on the motivation level of 11–12-year-old elementary school students, with significant variations in cognitive outcomes. Conclusion: The combination of active learning methods such as PBL and PjBL with high learning motivation is crucial for optimizing students' cognitive development, especially in critical thinking and problem-solving. Keywords: Problem-Based Learning; Project-Based Learning; Learning Motivation; Cognitive Development Abstrak: Pembelajaran dasar menjadi efektif melalui permainan, eksplorasi, dan diferensiasi, dengan pendekatan PBL, PjBL, serta motivasi tinggi guna meningkatkan kognitif, kreativitas, dan partisipasi anak. Tujuan penelitian mengukur efektivitas dua model pembelajaran dan motivasi belajar terhadap peningkatan kognitif anak yang mulai berpikir abstrak dan memecahkan masalah. Metode penelitian dengan pendekatan kuantitatif dengan desain eksperimen pretest-posttest control group, pengambilan sampel acak, penggunaan kuisioner, observasi, tes kognitif, uji normalitas, uji homogenitas, analisis Two Way ANOVA, uji post-hoc Tukey, dan analisis regresi linear berganda. Hasil penelitian menunjukkan: ada pengaruh signifikan metode pembelajaran dan motivasi belajar terhadap nilai kognitif anak. Kombinasi kedua faktor tersebut serta interaksinya secara statistik kuat memengaruhi perkembangan kognitif dengan daya prediksi 88,1%. Hasil ini menegaskan bahwa efektivitas metode pembelajaran bergantung pada tingkat motivasi siswa usia 11–12 tahun di sekolah dasar dengan variasi nilai kognitif yang signifikan. Kesimpulan: Kombinasi metode pembelajaran aktif seperti PBL dan PjBL dengan motivasi belajar tinggi sangat penting untuk mengoptimalkan perkembangan kognitif siswa, terutama dalam berpikir kritis dan pemecahan masalah. Kata kunci: Problem Based Leraning; Project Based Learning; Motivasi Belajar; Kognitif